Adherence to antihypertensive treatment among haemodialysis patients in the Yalgado Ouédraogo University Hospital, Ouagadougou, Burkina Faso: a cross-sectional survey - Bonzi, Yeremade Juste; Zoehinga, Patrice; Hien, Siébou; Sinon, Naadyatou B; Sanou , Gaoussou; Coulibaly, Gérard (African Journal of Nephrology, 2024)
Background: Hypertension prevails among haemodialysis patients, and its management is affected by fluid overload as well as patients’ adherence to medication and non-medication interventions. This study assessed the adherence to hypertensive medication by haemodialysis patients at the Yalgado Ouédraogo University Hospital in Ouagadougou, the first of its kind conducted in Burkina Faso. Methods: Face-to-face interviews were conducted to record haemodialysis patients with hypertension. The Girerd et al. compliance evaluation toolkit was used to assess therapeutic adherence. Patients were classified as observing poor or good adherence, based on whether they had three or more, or fewer than three, “yes” responses, respectively. The data were analysed using Stata software version 16. Descriptive statistics are presented as counts, percentage means, or medians. Results: The median age of the study sample of 75 haemodialysis patients was 44 years, and their median time on haemodialysis was 36 months. The median monthly estimated cost of antihypertensive drugs purchased per patient was US$ 25. Poor adherence was observed in 65 patients (illustrating minimal adherence problems and poor adherence). Reasons for poor adherence included the high cost of antihypertensive drugs, forgetfulness, and complex dosing regimens, cited by 45, 39, and 23 patients, respectively. Conclusion: The study revealed a high prevalence of poor adherence to antihypertensive treatment among the haemodialysis patients. This was attributed to unfavourable socio-economic conditions and the lack of universal health insurance.